The Role of UN Women in Addressing Women's Rights in Afghanistan under Taliban - Fahriyya Noor Ahsana; Nur Azizah (Journal of Islamic World and Politics, 2023)
The current condition of Afghanistan under the Taliban government creates considerable humanitarian problems, especially concerning the rights of women and girls. The Taliban threatens Afghan women by implementing several detrimental policies prohibiting them from going to school, working, and leaving the house. The Taliban restricted the movement of women workers and created an insecure space. This research aims to explain the role of UN Women in responding to humanitarian issues in Afghanistan, especially those related to women. This study used a descriptive method with literature sources such as books, journals, notes, and related reports. The findings indicated that UN Women is committed to assisting Afghan women in restoring their rights under Taliban rule. UN Women, as an International Organization, plays a role as an arena for Afghan women by facilitating women to speak, one of which is in a series of events at the UN Security Council Open Debate on Women, Peace, and Security, which was held at the UN Headquarters in New York. UN Women also works as a donor by providing financial assistance, which will be allocated to the needs of Afghan women. In addition, UN Women acts as an advocate through various activities.